Hydrochemical Characterisation and Assessment of the Level of Contamination of Groundwater Collected by Private Waterworks in the Town of Moundou in the South of Chad - Doumtoudjinodji, Prosper; DADELE, BERNADIN; Doumnang Mbaigane, Jean Claude (My University, 2024)
Groundwater is the main source of drinking water for large cities in most African countries. In Moundou, for example, the conventional groundwater supply system is failing. To compensate for this state failure, the population is building boreholes and wells, most of which tap the surface water table, gen erally referred to as the “water table”. The aim of this study is to characterize these waters in order to assess their level of contamination and, by extension, the degree of pollution of the water table. Major elements such as: Chloride (Cl−), Sulfate ( 2 4 SO−), Nitrate ( 3 NO−), Calcium (Ca2+), magnesium (Mg2+), so dium (Na+) and potassium (K+) were analysed by Liquid Chromatography and the Bicarbonate ion ( 3 HCO−) was determined by the titrimetric method. The methodology applied is based on a combination of hydrochemical tech niques and statistical analysis (PCA and CHA). A sampling campaign was carried out during high-water periods. The results of the physico-chemical analyses show mineralization ranging from 7.29 to 3670 μS/cm, with an av erage of 487.44 μS/cm. The groundwater studied is generally acidic, with a pH ranging from 3.26 to 6.41. Based on their anions, they are classified into four main hydrochemical facies: chloride and sulphate facies, calcium and magne sium facies, sodium and potassium facies and bicarbonate facies. The various correlations between major ions and statistical analyses have enabled us to identify three hydrogeochemical processes involved in water mineralization. The dominant process is silicate hydrolysis, followed by cation exchange, then anthropogenic input, which influences mineralization by polluting the water.
Keywords: Drinking Water; Groundwater; Chemical Pollution; Moundou Chad